Dynamism, Sensitivity, and Consequences of Mesenchymal and Stem-Like Phenotype of Cancer Cells - Petra Gener; Joaquin Seras-Franzoso; Patricia González Callejo; Fernanda Andrade; Diana Rafael; Francesc Martínez; Sara Montero; Diego Arango; Joan Sayós; Ibane Abasolo; Simó Schwartz (Stem Cells International)
There are remarkable similarities in the description of cancer stem cells (CSCs) and cancer cells with mesenchymal phenotype. Both cell types are highly tumorigenic, resistant against common anticancer treatment, and thought to cause metastatic growth. Moreover, cancer cells are able to switch between CSC and non-CSC phenotypes and vice versa, to ensure the necessary balance within the tumor. Likewise, cancer cells can switch between epithelial and mesenchymal phenotypes via well-described transition (EMT/MET) that is thought to be crucial for tumor propagation. In this review, we discuss whether, and to which extend, the CSCs and mesenchymal cancer cells are overlapping phenomena in terms of mechanisms, origin, and implication for cancer treatment. As well, we describe the dynamism of both phenotypes and involvement of the tumor microenvironment in CSC reversion and in EMT.